The day I die : the untold story of assisted dying in America - Hannig, Anita (Sourcebooks, 2022)
"The Day I Die is a major work of nonfiction that tackles the one issue we'll all eventually come to face-our final days, hours, and minutes. With clarity and empathy, award-winning anthropologist Anita Hannig uncovers the stigma against the practice of assisted dying, untangles the legalities and logistics of pursuing an assisted death in America today, and profiles the dedicated advocates and medical personnel involved. In intimate, lyrical detail, Hannig explains why someone might choose an assisted death and how that decision impacts their loved ones. In a time when nearly 80 percent of Americans die in hospitals and nursing homes, medical assistance in dying could transform the way we die for the better, allowing more people to define the terms of their own death"--